Emotional Intelligence and Psychological Adjustment among Doctors and Nurses in a Tertiary Care Hospital in Rawalpindi-Pakistan: A Cross Sectional Study - Malik, Naushaba; Malik, Minaal Ahmed; Aftab, Shahbakht; Noor, Rida; Khalid, Usman; Shahzad, Tayyaba (Journal of Rawalpindi Medical College, 2023)
Objective: This study aimed to determine the relationship between EI and the quality of nursing care from the viewpoint of nurses and patients. Methods: This cross-sectional study was conducted at a public sector tertiary care hospital in Rawalpindi, Pakistan, over 6 months from November 2019 to April 2020. The convenience sampling technique was employed. The study groups were qualified practising doctors and nurses including nursing assistants and paramedics. Study groups were provided with a self-administered questionnaire that was filled out after getting consent from the study participants. Data analysis was done by entering it into SPSS version 22. The relationship between emotional intelligence and psychological adjustments among the two groups was assessed by applying an independent T-test. Results: The current study explored that doctors were emotionally intelligent and psychologically well-adjusted as compared to nurses. Females were more emotionally intelligent than males; however, males were better adjusted psychologically. Years of experience had no significant results between both groups, while there was a positive correlation between the department of practice and psychological well-being. Conclusions: It shows that harmonious work environments and friendly interpersonal relationships positively affect the well-being of HCWs and patients. What this indicates is a need to bring about changes within work environments to produce friendly interpersonal relationships and a positive impact on the well-being of HCWs and patients. Keywords: Emotional intelligence, Psychological adjustments, Nursing staff